ABNORMAL RETURN (AR) AND TRADING VOLUME ACTIVITY (TVA) ON FIRM VALUE IN BANKING COMPANIES IN INDONESIA - Wiwit Hariyanto; Endra Wahyu Ningdiyah; Fitiyan Izzah Noor Abidin (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: The study aims to evaluate the influence of Abnormal Return (AR) and Trading Volume Activity (TVA) on the Firm Value of banking companies in Indonesia during the 2019-2023 period. Methods: This quantitative research utilizes secondary data from 13 banking companies selected through purposive sampling, yielding a total of 65 observations (13 companies × 5 years). Data were analyzed using multiple linear regression, processed with SPSS version 27. Results: The findings reveal that both Abnormal Return and Trading Volume Activity significantly influence the Firm Value of banking companies in Indonesia during the specified period. Novelty: This study contributes to the literature by focusing on the dual impact of AR and TVA on Firm Value specifically within the banking sector in Indonesia, providing insights into financial performance dynamics during the 2019-2023 period.